Building A Culture Of Safety: Evaluating Safety Education In Indonesian Multimodal Transportation Programs - Markus Yando; Marudut Bernadtua Simanjuntak (International Journal of Multilingual Education and Applied Linguistics, 2024)
This research critically evaluates the effectiveness of safety education within Indonesian multimodal transportation programs, focusing on promoting a culture of safety among cadets. Qualitative research methods were employed, involving 50 cadets studying various aspects of multimodal transportation, logistics, transportation safety, and law and road management. The study examines the cadets' understanding and application of safety principles, aiming to identify strengths and areas for improvement in safety education. The findings contribute to enhancing safety practices in the Indonesian transportation sector and serve as a foundation for future research and policy development.